2021
DOI: 10.4103/aja.aja_50_20
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ipsilateral testicular atrophy on semen quality and sperm DNA fragmentation response to varicocele repair

Abstract: Varicoceles adversely impact semen quality and sperm DNA fragmentation, which typically improve with surgical repair. Some men with varicoceles have ipsilateral testicular atrophy due to damage from the varicocele. This study assessed semen quality and the sperm DNA fragmentation index (DFI) response to varicocele repair in men with ipsilateral testicular atrophy (TA) versus men with no testicular atrophy (NTA). Semen parameter values and DFI in both groups were compared preoperatively and postoperatively. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Finally, 29 studies assessing the impact of VR on SDF and MDA were included in the present analysis ( Fig. 1 ) [ 34 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 29 studies assessing the impact of VR on SDF and MDA were included in the present analysis ( Fig. 1 ) [ 34 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…The data show that 50% of recurrent miscarriage causes still cannot be shown, among which the male factor is an important aspect. Current studies have made it clearer that the main causes of male factors include severe sperm deformity, sperm DNA damage, and men's own chromosome abnormality 23 . Although some patients are still unable to determine the cause after a series of tests, studies suggest that avoiding certain adverse factors can benefit some patients, access to fertility.…”
Section: Male Factorsmentioning
confidence: 99%
“…Current studies have made it clearer that the main causes of male factors include severe sperm deformity, sperm DNA damage, and men's own chromosome abnormality. 23 Although some patients are still unable to determine the cause after a series of tests, studies suggest that avoiding certain adverse factors can benefit some patients, access to fertility. The direct causes of these sperm quality problems are varicocele, sperm membrane lipid peroxidation, and abnormal oxidative stress.…”
Section: Male Factorsmentioning
confidence: 99%
“…The indications for varicocelectomy in infertile patients are still debated. Some studies have shown improvements in semen quality, DNA fragmentation, and pregnancy rates after varicocele repair ( 8 , 9 ). However, other clinical investigations have reported unsatisfactory outcomes in infertile patients ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%